Assessment of low fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) on clinical, psychology and quality of life outcomes assessed in patient with irritable bowel syndrome (IBS) in Hospital Universiti Sains Malaysia (HUSM), Kelantan - Isa, Adib Mat (2020)
diet with low content of fermentable short-chain carbohydrates (fermentable oligo-, di-, monosaccharides and polyols, FODMAPs) has been reported to be effective in the treatment of patients with irritable bowel syndrome (IBS). Therefore, the study aimed to compare the effect of a low FODMAP diet on IBS symptom in outpatients with IBS. The IBS adults of Malaysian population offers a unique opportunity to study the interaction between gut microbiota, diet, and functional GI symptoms. We performed a study of 18 patients who met the Rome III criteria for IBS, enrolled at gastroenterology outpatient clinics in Kubang Kerian. Subjects were assigned to groups that eat specific diets for 4 weeks: a diet low in FODMAPs (n=18), with greater emphasis on how and when to eat rather than on what food to ingest. Symptom severity was assessed using the IBS-SSS, HADS, EQ-5D and bloat questionnaires, and the patients completed a 3-day food diary during the intervention. A number of six healthy controlled subjects were enrolled (n=6). The analysis was based on the intention to treat. The IBS patients (n=18) were assessed based on the baseline symptoms and symptoms after 4 weeks of interventions. There were no significant differences in median score for pre- and post- IBS-SSS score (p=0.054) in IBS patients. For patient’s bloat, there were significant differences in the median score for pre- and post-score of SevGen (generalized bloat severity), Sev24 (24 hours bloat severity) and quality of life for bloat in IBS patients (p=0.043, p=0.007, p=0.010 respectively). We concluded that a low FODMAP diet did not show effectiveness in IBS patients’ symptoms. Nevertheless, there was a significant difference between Malay and Chinese ethnicity alone in IBS symptoms. Besides, quality of life and generalized bloat had significant differences. Low FODMAP diet can be an alternative to reduce bloat and improve quality of life in IBS. Further larger studies are required to represent the IBS population locally.